If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (n + -4)(n + 4) = n + -4 Reorder the terms: (-4 + n)(n + 4) = n + -4 Reorder the terms: (-4 + n)(4 + n) = n + -4 Multiply (-4 + n) * (4 + n) (-4(4 + n) + n(4 + n)) = n + -4 ((4 * -4 + n * -4) + n(4 + n)) = n + -4 ((-16 + -4n) + n(4 + n)) = n + -4 (-16 + -4n + (4 * n + n * n)) = n + -4 (-16 + -4n + (4n + n2)) = n + -4 Combine like terms: -4n + 4n = 0 (-16 + 0 + n2) = n + -4 (-16 + n2) = n + -4 Reorder the terms: -16 + n2 = -4 + n Solving -16 + n2 = -4 + n Solving for variable 'n'. Reorder the terms: -16 + 4 + -1n + n2 = -4 + n + 4 + -1n Combine like terms: -16 + 4 = -12 -12 + -1n + n2 = -4 + n + 4 + -1n Reorder the terms: -12 + -1n + n2 = -4 + 4 + n + -1n Combine like terms: -4 + 4 = 0 -12 + -1n + n2 = 0 + n + -1n -12 + -1n + n2 = n + -1n Combine like terms: n + -1n = 0 -12 + -1n + n2 = 0 Factor a trinomial. (-3 + -1n)(4 + -1n) = 0Subproblem 1
Set the factor '(-3 + -1n)' equal to zero and attempt to solve: Simplifying -3 + -1n = 0 Solving -3 + -1n = 0 Move all terms containing n to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1n = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1n = 0 + 3 -1n = 0 + 3 Combine like terms: 0 + 3 = 3 -1n = 3 Divide each side by '-1'. n = -3 Simplifying n = -3Subproblem 2
Set the factor '(4 + -1n)' equal to zero and attempt to solve: Simplifying 4 + -1n = 0 Solving 4 + -1n = 0 Move all terms containing n to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1n = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1n = 0 + -4 -1n = 0 + -4 Combine like terms: 0 + -4 = -4 -1n = -4 Divide each side by '-1'. n = 4 Simplifying n = 4Solution
n = {-3, 4}
| 2x-5=55+7x | | -(3)/(y-5)=(-(8)/5y-25)+1 | | -6(x+4)+158=13+25 | | t(3t+27)=66 | | -4/6x=12/24 | | 4x+56=5432 | | 5+7x=-x+53 | | -(2x^2y+4z)+4z-7x^2y= | | 8-2w=2 | | -2/6x=6/12 | | 84=12(12y+3) | | 2x+3*x-1= | | 7x-43=52 | | 3X+3/5=-2X-7/4 | | 4x^2-20x+10=0 | | -14-(-12)=x/2 | | 7-3(5t-10)=-67 | | x+3=12-1x | | 49=3x+9 | | -5x-10=2x+11 | | 52=3x+7 | | 17x+30=4(3x+6)+5x+6 | | 7y+3(y-9)=6(y+1)-2 | | 9(y-6)/2=-2y | | -29+7+(-18)+(-12)= | | -(25x+15y+80)= | | -5(3t-2)+4t=2t-7 | | 0/-22 | | -112/-21*-20 | | -4(2t-2)+3t=4t-6 | | xy+5x-10+2y= | | -2(4x-1)+9=-8x+11 |